Transformasi Nilai-Nilai Sosial Dalam Budaya Masyarakat Era Teknologi Informasi Di Desa Paladang Kabupaten Enrekang - Ramlah, Adhe Irma; Ashar, Muhammad; Padli, Feri; Falihin, Dalilul (xxxx-xxxx, 2024)
This research aims to: 1). Knowing the social values in the culture of society in the information technology era, 2). Knowing what consequences arise from changes in society's social values in the era of information technology, 3). Knowing how to defend culture from the influence of technology The results of this research show that: 1). The socio-cultural values that exist are mutual cooperation in cleaning the yard, mutual cooperation in cleaning the sidewalk, mutual cooperation in cleaning the mosque, cooperation in various matters, mutual help, solidarity, harvest festivals, sipulung culture and kabo marassi culture. 2). The positive consequences that arise are making communication easier, making it easier to get information and making work or activities easier. Meanwhile, the negative impacts that arise are reduced interaction, addiction to playing games and the emergence of foreign cultures. 3). Efforts are made to maintain culture. Teaching culture to the younger generation, preserving culture and limiting the use of technology.